On the impossibility of sustainable growth in a manufacturing based economy - Yoon, Sang Won; Yoon, Chang-Ho (Economic Research-Ekonomska Istraživanja, 2018)
This paper investigates a possibility of sustainable growth in a multi-output endogenous growth framework where the capital accumulation takes place mainly through the production of the dirty manufactured goods. It is shown that in a closed economy, economic growth is not environmentally sustainable, even under an optimal pollution tax unless the consumption elasticity of substitution between clean and dirty goods approaches infinity as in a small open economy which exports dirty goods. There exists a minimal threshold level of the ratio of clean to dirty capital that ensures sustainable growth in a closed economy.
Keywords: Kuznets curve; Sustainable growth; consumption behavior; dept.eco; economic growth; elasticity; elasticity of marginal utility; elasticity of substitution; environmental Kuznets curve; peer-reviewed; sustainable development

Sustainable growth with pollution augmenting technological changes - Yoon, Sang Won; Yoon, Chang-Ho (2023)
Disruptive technological changes, including carbon capture and storage, can have macroeconomic rebound effects that pose a threat to long term environmental sustainability when not accompanied by pollution taxes. The paper demonstrates that when the elasticity of intertemporal substitution is less than one, implementing a Pigouvian tax effectively stabilizes pollution emissions, regardless of technical and consumption elasticities of substitution. However, if the elasticity of intertemporal substitution exceeds one, flexibility in technical or consumption substitution could cause sustainable growth to falter. The policy implications concerning the role of subsidies for clean technology are discussed.
Keywords: Elasticity of intertemporal substitution; Optimal pollution tax; Sustainable development; dept.eco; energy rebound; technological change

Bilateral environmental aid under trade competition - Yoon, Sang; Kim, Younjun; Park, Byoung; Yoon, Chang-Ho (Applied Economics Letters, 2026)
Keywords: Bilateral environmental aid; Bilateral trade; Competition (biology); Environmental impact assessment; Environmental policy; Trade barrier; climate finance; dept.eco; energy-saving aid; strategic aid allocation; trade competition

ICT and transport infrastructure development: an empirical analysis of complementarity - Na, Kyoung Y.; Kim, Dong H.; Park, Byoung G.; Yoon, Sang W.; Yoon, Chang-Ho (Applied Economics, 2020)
This paper provides an empirical framework to assess the nonlinear complementary linkage effects that arise from the interaction between motorway capital and information and communications technology (ICT) capital in developed economies. Using panel data from the Organisation for Economic Co-operation and Development (OECD) member countries and controlling for endogeneity, the paper finds that there exists a critical mass for ICT capital such that if the capital grows beyond the critical mass, the marginal contribution of motorway capital to productivity growth increases as the motorway is extended. This empirical result explains variations in the productivity contributions of transport infrastructure across countries that differ in their ICT infrastructure and has implications for setting the investment priorities of key components of infrastructure. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: ICT capital; OECD; complementarity; dept.eco; empirical analysis; information and communication technology; infrastructural development; infrastructure development; motorway; panel data; peer-reviewed; productivity; productivity growth; transportation infrastructure